Electrode assembly and method for preparing the same

By applying thermoplastics in the catalyst-free edge area of ​​the PTFE film of the air cathode, a mixed layer that prevents electrolyte seepage is formed, and the air cathode is closely combined with the battery frame, the electrolyte seepage of the existing air cathode in a highly alkaline environment is solved. Problem, improving the stable performance and service life of the battery.

CN112534628BActive Publication Date: 2025-02-21PHINERGY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN201980038569.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-06-06
Filing Date
2019-06-06
Publication Date
2025-02-21
Estimated Expiration
2039-06-06

AI Technical Summary

Technical Problem

The existing air cathode is prone to electrolyte seepage in a highly alkaline environment, resulting in a degradation of battery performance.

Method used

By applying thermoplastics in the catalyst-free edge region of the PTFE film, a mixing layer is formed to prevent electrolyte seepage and tightly bond the air cathode to the battery frame.

Benefits of technology

It effectively reduces the leakage of electrolytes, improves the stability of the air cathode, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112534628B_ABST
    Figure CN112534628B_ABST
Patent Text Reader

Abstract

The invention relates to a metal-air electrochemical cell, the cell comprising a frame (100) defining an electrolyte chamber having an anode side and a cathode side, wherein an air cathode assembly is provided in the cathode side, the air cathode assembly (20) comprising a hydrophobic porous membrane having a first face and a second face, a current collector (21) and a catalyst-containing active layer (26) being provided on the first face, the planar dimensions of the catalyst-containing active layer on the first face being smaller than the planar dimensions of the hydrophobic membrane and the current collector, so that the catalyst-containing active layer does not reach the edges of the hydrophobic membrane and the current collector, thereby creating a catalyst-free margin (27) around the catalyst-containing active layer on the hydrophobic membrane (31) and the current collector, and wherein the first face of the hydrophobic membrane and the frame of the cell are bonded together by a thermoplastic (101) applied to the catalyst-free margin of the hydrophobic membrane. A method of assembling a metal / air cell is also described.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to an electrode assembly which is particularly suitable for use as an air cathode in metal / air cells and batteries and as an air cathode in fuel cells containing an alkaline electrolyte.

[0002] In its most common form, the operation of a metal / air electrochemical cell is based on the reduction of atmospheric oxygen at the cathode and oxidation of a metal anode. The aqueous electrolyte present in the cell is a highly alkaline solution, such as a highly concentrated potassium hydroxide solution. Figure 1 A typical configuration of a metal / air battery is schematically illustrated, showing an air cathode, a consumable metal anode, and an electrolyte.

[0003] A commonly used air cathode is composed of: (i) a conductive mesh, expanded foil or metal foam used as a current collector, (ii) active electrode particles (including a catalyst that promotes the reduction of oxygen) provided in the current collector, and (iii) a hydrophobic porous membrane (polytetrafluoroethylene, abbreviated as PTFE, PTFE) supported on one face of the mesh or foil. The air-permeable, water-impermeable, hydrophobic PTFE membrane faces the outside of the electrochemical cell, while the catalytically active layer faces the aqueous electrolyte.

[0004] The anode immersed in the electrolyte is made of metals such as aluminum, zinc, magnesium, iron and their alloys. When an aluminum anode is used, the battery is a primary cell. In other words, when the aluminum anode is consumed, the battery is recharged by replacing the consumed aluminum anode with a new anode. The discharge reaction of the aluminum-air battery is as follows:

[0005] 4Al+3O2+6H2O→4Al(OH)3

[0006] The solid aluminum hydroxide precipitated on the anode side is collected and withdrawn from the cell.

[0007] The aluminum-air battery is composed of a plurality of individual cells as described above, arranged in a stacked relationship to form a rectangular structure held together by conventional mechanical members, such as a plurality of rods, extending along each longitudinal opposite side of the battery and in conjunction with a support member, which is positioned in the other side of the battery, for example in the form of a separator. The battery is equipped with circulation and exhaust members for exposing the cathode to an oxygen atmosphere. Such a battery can be used as a power source for an electronic vehicle. Each individual cell in the battery has a frame defining an electrolyte cavity. The frame is typically molded integrally from a chemically inert material, i.e., capable of withstanding a strongly alkaline environment. Thermoplastic materials such as polypropylene, polyethylene, FEP, PTFE, Noryl and Santoprene are typically used to produce these frames. One side of the electrolyte cavity contains an aluminum plate, and the opposite side is sealed by an air cathode. Reference is made below Figure 5Give a description of the frame of such a battery.

[0008] The present invention resides in the structure of the air cathode and its attachment to the frame of the battery. As described above, the air cathode is generally composed of an air-precursor PTFE membrane, a catalytically active layer applied on one face of the PTFE membrane, and a current collector (e.g., a metal mesh) embedded in the catalytically active layer. The PTFE membrane, the active layer, and the metal grid correspond in geometry and size. For example, US 3,553,024 describes the preparation of a catalytically active material in the form of a paste, which is composed of platinum black and a binder (colloidal PTFE) dispersed on one face of the PTFE membrane. Then, a piece of platinum gauze of the same size as the PTFE membrane is placed on the coated surface of the PTFE membrane and pressed into the membrane. The resulting structure is dried and sintered. In other words, a coextensive design is generally used for the air cathode, that is, the PTFE membrane and the catalytically active layer deposited thereon have the same size. A similar coextensive design is also found in US 4,925,744. The air cathode can have a cathode metal frame, which is then fixed to the frame of the battery defining the electrolyte cavity frame.

[0009] In co-assigned WO 2014 / 057483, we report that the co-extension design is prone to electrolyte leakage. In other words, aqueous electrolytes cannot flow through and percolate through the PTFE membrane due to the highly hydrophobic nature of the membrane. However, electrolyte percolation still occurs because the electrolyte flows down over the inner surface of the PTFE membrane and leaks through the interface between the membrane and the mechanical gasket applied on its edge (e.g., an O-ring that does not typically adhere well to the membrane). Electrolyte leakage and electrolyte loss can negatively impact the performance of the air cathode and the metal / air battery utilizing the cathode.

[0010] As shown in WO 2014 / 057483, by replacing the coextensive design with a different design, the problem of electrolyte leakage can be minimized and stable performance of the air cathode in the air / aluminum battery can be achieved over a long test period. In other words, in the air cathode assembly described in WO 2014 / 057483, the planar dimensions of the catalytically active layer are smaller than the planar dimensions of the PTFE membrane and the current collector pressed thereon, so that the catalytically active layer cannot reach the edges of the PTFE membrane and the current collector.

[0011] Figure 2The design disclosed in WO 2014 / 057483 is illustrated. The active layer containing catalyst and the current collector screen are indicated by reference numerals 26 and 21, respectively. The PTFE membrane is indicated by reference numeral 31; the arrow indicates that the PTFE is placed below the current collector 21 and the active layer containing catalyst 26. Reference numeral 22 is a metal piece bonded (e.g. by welding) to one side of the current collector 21 to increase the current collection; the current is withdrawn via the contact sheet 24. Due to the different planar dimensions between the active layer containing catalyst 26 on the one hand and the current collector 21 and the PTFE membrane 31 on the other hand, there is a catalyst-free marginal area 27 of the PTFE membrane. That is, the screen pressed against the PTFE membrane is not covered by the catalyst. It is shown in WO 2014 / 057483 that the pores of the PTFE membrane in the catalyst-free marginal area 27 can be blocked by means of a suitably diluted epoxy formulation, which can flow into the pores of the PTFE membrane. Upon drying and removal of the volatile solvent, a narrow boundary layer containing sealant is created that delimits the area of ​​the coated PTFE membrane. When the electrode assembly is affixed to the frame of the electrochemical cell placed in the aluminum / air battery, the penetration of the sealant into the PTFE membrane, which causes the pores of the membrane to be partially filled, can form a good mechanical barrier for electrolyte percolation. Other sealants mentioned in WO2014 / 057483 include silicones, polyurethanes, acrylates, rubbers or rubber-like materials.

[0012] We now propose an alternative method to utilize the catalyst-free peripheral area of ​​the PTFE membrane in the air cathode assembly disclosed in WO 2014 / 057483. The method is based on causing molten thermoplastic to flow under applied pressure into the pores of the PTFE membrane in the catalyst-free area (i.e., where the mesh is not covered by the catalyst) and to tightly bond the air cathode assembly and the frame of the cell together.

[0013] Use the following reference Figure 4 and 5 The electrode assembly based on this method is manufactured to study the permeability of a molten thermoplastic - polypropylene - into the pores of a PTFE membrane (but without the metal current collector for the sake of simplicity of the procedure). The electrode assembly is then cut transversely to expose a cross section of the PTFE membrane in a catalyst-free marginal area. The exposed side is studied with the aid of a scanning electron microscope (SEM) equipped with an X-ray energy dispersive spectroscopy system (EDX; EDAX), which allows the identification of specific elements and their relative proportions (weight or atomic %). For example, the energies of the characteristic lines assigned to carbon and fluorine in the EDX spectrum are respectively 0.27keV and 0.67keV. We refer to the exposed side as the side of the electrode assembly; assuming Figure 2If the planar electrode assembly is located in the XY plane, the side of the electrode assembly extends above the YZ plane.

[0014] Figure 3A , 3B 3C show SEM images of the side of the electrode and corresponding EDX spectra named "Spectrum 1", "Spectrum 2" and "Spectrum 3" associated with each of the three different layers seen in the SEM image of the PTFE membrane. It can be seen that the thickness of the PTFE membrane is 500μm. It should be remembered that complete PTFE consists only of carbon and fluorine atoms (the molecular formula of PTFE is –[CF2-CF2]- n ), while fluorine is the main component in terms of weight and atomic %. Therefore, the changes in the relative proportions of carbon and fluorine measured by the EDX analyzer at different points across the thickness of the PTFE membrane indicate that the PTFE membrane has undergone compositional changes due to the added thermoplastic. In other words, a high constant fluorine concentration represents a "native" PTFE membrane; a zone of reduced fluorine concentration corresponds to a "mixed" thermoplastic-containing PTFE segment.

[0015] Table 1 lists the weight and atomic percent concentrations of the PTFE membrane modified according to the present invention measured by EDX analyzer.

[0016] Table 1

[0017]

[0018]

[0019] *In addition to carbon, other elements were detected, mainly oxygen

[0020] From the results set forth in Table 1, it can be seen that no fluorine was detected in the top layer, which corresponds to the polypropylene coating applied to the catalyst-free margin of the PTFE membrane. In contrast, the composition of the bottom layer is completely consistent with intact PTFE, with fluorine and carbon being the major and minor elements, respectively. The middle layer exhibits a mixed nature: fluorine is detected, but it is a minor component, because the fusion of polypropylene within the pores in the PTFE membrane pores leads to a significant increase in the carbon content in the middle layer. The middle layer illustrates a good barrier created to minimize electrolyte percolation.

[0021] The results also show that Figure 3D and 3E In, with the help of Figure 3D and 3E The carbon and fluorine peak intensities are plotted relative to the position along the side of the PTFE membrane. Intermediate layers are clearly seen where both carbon and fluorine are detected as major and minor components, respectively; moving from the bottom layer to the top layer, the carbon content increases and the fluorine content decreases (blue and red, respectively).

[0022] Thus, the present invention is primarily directed to an electrode assembly comprising a PTFE membrane having a first face and a second face, a current collector and a catalyst-containing active layer being provided on the first face, wherein the planar dimensions of the catalyst-containing active layer are smaller than the planar dimensions of the PTFE membrane and the current collector, such that the catalyst-containing active layer does not reach the edges of the PTFE membrane and the current collector, thereby creating a catalyst-free margin around the catalyst-containing active layer on the PTFE membrane, wherein a thermoplastic is applied on the first face in the region of the catalyst-free margin, and wherein EDX spectroscopy indicates variations in the relative proportions between fluorine and carbon over the thickness of the PTFE membrane in the catalyst-free margin, thereby identifying segments in which carbon and fluorine are the major and minor elements, respectively; said segments typically lack other elements such as oxygen. These "mixed" segments are typically located at a distance of 0 to 100 μm measured from the first ("inner") face of the PTFE membrane.

[0023] The present invention also relates to a metal-air electrochemical cell, which includes a frame defining an electrolyte chamber having an anode side and a cathode side, wherein an air cathode assembly is arranged in the cathode side, the air cathode assembly including a hydrophobic porous membrane (especially PTFE) having a first side and a second side, a current collector and a catalyst-containing active layer are arranged on the first side, the planar size of the catalyst-containing active layer on the first side is smaller than the planar size of the hydrophobic membrane and the current collector, so that the catalyst-containing active layer does not reach the edge of the hydrophobic membrane and the current collector, thereby creating a catalyst-free margin around the catalyst-containing active layer on the hydrophobic membrane and the current collector, and wherein the first side of the hydrophobic membrane and the frame of the cell are bonded together (i.e., welded) by thermoplastic applied to the catalyst-free margin of the hydrophobic membrane.

[0024] Thermoplastics (e.g., one or more polyolefins, particularly polypropylene) coat the mesh current collector and / or penetrate into the pores of the hydrophobic membrane in the catalyst-free margins of the air cathode. For hydrophobic membranes made of PTFE, information collected from EDX spectroscopy as described above can be used to indicate the presence of thermoplastics in the pores of the PTFE membrane by evaluating the variation in the relative ratio between fluorine and carbon in the thickness direction of the PTFE membrane in the catalyst-free region of the air cathode welded to the cell frame.

[0025] In a variation of the invention, the thermoplastic applied to the catalyst-free margin of the hydrophobic membrane comprises a primary polymer and a secondary polymer, such as polypropylene and a second polyolefin, respectively. As illustrated below with reference to the manufacture of a battery, we have found it beneficial to use a combination of (i) polypropylene as the primary thermoplastic (due to its ability to penetrate the pores of the PTFE membrane in the molten state under applied pressure, creating a strong mechanical weld), and (ii) a second polyolefin having appropriate flowability and melt viscosity (to provide an additional leak-proof barrier).

[0026] The present invention additionally provides a metal-air battery comprising a plurality of individual cells as described above mounted in an array.

[0027] The manufacture of the electrode assembly will now be described with reference to the accompanying drawings. Figure 4 The generation of an air cathode having the design disclosed in WO 2014 / 057483 is illustrated ( Figure 4 Based on WO 2014 / 057483 Figure 5 , where the final step - epoxy addition - which has been modified by the present invention is omitted). Then, Figure 5 The invention is provided to demonstrate a simple method of replacing epoxy sealants with thermoplastics to minimize electrolyte leakage from a battery. Accordingly, the invention provides a method for assembling a metal / air battery, comprising the following steps:

[0028] (i) providing an air cathode assembly comprising a hydrophobic porous membrane having a first surface and a second surface, wherein a current collector and an active layer containing a catalyst are provided on the first surface, wherein the planar size of the active layer containing the catalyst is smaller than the planar size of the membrane and the current collector, and the active layer containing the catalyst does not reach the edge of the membrane and the current collector, thereby creating a catalyst-free margin [the width of the margin (W)] on the membrane and the current collector surrounding the active layer containing the catalyst 边限 ) is preferably between 1 and 10 mm, for example around 3 to 8 mm];

[0029] (ii) placing the cathode assembly on top of a battery frame defining an electrolyte cavity, wherein a thermoplastic body, which is capable of softening to a movable, flowable state when heated to an elevated temperature (e.g., in the range of 120° C. to 280° C.), is positioned between the battery frame and the cathode assembly, wherein the thermoplastic body coincides with the catalyst-free boundary region in geometry and position, and also substantially coincides with the catalyst-free boundary in width [the raised thermoplastic portion (W 热塑性 ) is generally slightly smaller than the width of the catalyst-free margin; for example, W 热塑性 +0.1-3.0mm=W 边限 ];as well as

[0030] (iii) applying heat and pressure to soften the thermoplastic body and force it to flow in the direction of the pores in the catalyst-free confines of the hydrophobic membrane, thereby welding the air cathode assembly to the frame of the cell as the molten mass solidifies.

[0031] The hydrophobic porous membrane is preferably a PTFE membrane (comprising a PTFE layer, for example, formed by spraying an ink formulation, drying and pressing) or a gas diffusion layer (GDL) membrane.

[0032] The thermoplastic body is preferably made of polypropylene and is preferably configured as a raised portion of the cell frame - i.e., in the form of a thin wall 1-4 mm high - which protrudes from the surface of the frame and forms an integral part of the frame. As mentioned above, the geometry of the thermoplastic raised portion matches the geometry of the catalyst-free area in the air cathode. When melting the raised portion of the cell frame, the thermoplastic flows in the direction of the catalyst-free area in the cathode assembly to weld the two components (frame and air cathode).

[0033] The manufacturing method preferably includes the steps of applying a second polymer such as a hot melt polyolefin (e.g., as a bead) to the surface of the battery frame, adjacent to the raised portion of the battery frame and in an outward direction from the raised portion of the battery frame so that the hot melt polyolefin surrounds the raised portion. This combination of the primary thermoplastic and the second hot melt polyolefin creates a strong mechanical weld as well as an additional leak-proof barrier.

[0034] The cathode assembly may also be preheated prior to the welding step.

[0035] from Figure 4Initially, a rectangular or square metal screen (21) is used as a current collector (23) together with a solid metal piece (22) attached to one side of the screen. As explained below, other shapes are also suitable. The screen (21) is made of a metal selected from the group consisting of nickel, nickel-plated copper, stainless steel, tin, bismuth, silver and alloys thereof, with nickel being particularly preferred. The mesh size is 10 to 500 meshes and the thickness is 20 μm to 500 μm. Suitable screens are commercially available (e.g. from Gerard Daniel Worldwide), such as a nickel grid with a lead diameter of 70-75 μm and a mesh opening of 200 μm. Other options for current collectors include (i) expanded foils, which result from a process in which holes are formed in a metal foil and then the holes are mechanically expanded (e.g., expanded foil from Dexmet Corporation (5Ni5-050P); and (ii) foams, which are three-dimensional porous structures of a certain type of metal. Regardless of their specific shape, for the purpose of simplicity, current collectors are sometimes referred to herein as "meshes," "grids," or "screens."

[0036] exist Figure 4 In the illustrated embodiment, the solid metal piece (22) corresponds in length to the grid dimensions and is also provided with a contact piece (24). The function of the element (22) is to increase current collection. It is preferably made of copper, nickel or nickel-plated copper and has a thickness between 25 μm and 3 mm. It is seen that although only one side of the grid is modified to have the piece (22) for improved current collection, it should be understood that the additional sides can be modified similarly. For example, the current collector can be provided by a highly conductive metal frame, the open area of ​​which corresponds substantially in shape and size to the mesh (21). In such a case, the outer dimensions of the frame are approximately (3 to 40 cm) x (3 to 40 cm), and the inner dimensions of the frame are slightly smaller than the outer dimensions, for example, the inner dimensions are about 0.5-2 cm shorter than the outer dimensions. The mesh (21) can be attached to one or more pieces (22) or to a complete frame to form a current collector by the method described in WO 2014 / 057483, for example by means of a conductive adhesive material (e.g., conductive epoxy) or welding (e.g., spot welding, laser welding, ultrasonic welding or soldering). Appropriate techniques are applied to ensure low resistance and multiple flow paths for the current; for example, when spot welding is applied, welding must be performed at a sufficient number of points. Preferably, the mesh (21) is made of nickel and the conductive metal piece (22) (or the entire frame) is made of nickel-plated copper, wherein the thickness of the nickel plating provided on the copper frame is 1 to 50 μm.

[0037] As described further below, Figure 2The reference number (25) in the figure indicates the "tray" used in the printing step. The current collector (23) is placed on the "tray", and a printable composition comprising a catalyst and an adhesive that can be used in the oxygen reduction reaction is applied to the central area of ​​the metal grid current collector to form a catalytically active layer (26). The preferred printable composition for creating the catalytically active layer is described below. Note that the margin area (27) of the metal grid current collector is free of catalytically active material. The catalyst-free margin area (27) surrounding the catalytically active layer (26), that is, the gap between the edge of the current collector and the central area filled with active material, is between 1 mm and 14 mm wide. More preferably, the width of the margin area (27) is between 1 and 10 mm, for example, around 3 to 8 mm.

[0038] The catalyst-free delimited areas of the metal grid are coated with an adhesive (e.g., FEP), then a porous hydrophobic PTFE membrane (31), preferably slightly larger than the metal grid (21), is attached to the metal grid and pressure is applied to the structure to achieve good contact between the hydrophobic membrane (31) and the active catalytic layer (26). PTFE membranes with a thickness of 10 to 400 microns can be used and are commercially available from Saint Gobain or Gore.

[0039] Note that different orders of steps can be used ( Figure 4 (not shown), for example, a layer of the catalyst composition (26) can be first printed on a PTFE membrane (31), and then the metal grid current collector (23) can be pressed into the coated PTFE membrane. Regardless of the order of the steps, the resulting structure consisting of the PTFE membrane, the catalytically active layer and the current collector is then heat treated, i.e., baked and sintered at about 240 to 320° C. for 1 to 60 minutes.

[0040] The application of the catalytically active layer (26) to the mesh (21) is now described in more detail. As noted above, the catalytically active layer (26) is preferably printed as described in detail in WO2014 / 057483. As an alternative to the printing technique, the catalyst composition consisting of the catalytically active particles and the binder can be formulated into a paste, which can be dispersed directly on the central area of ​​the hydrophobic membrane by any convenient technique, or the catalyst and binder can be applied in the form of a dispersion that can be spin-coated on the membrane, and then the metal grid current collector is pressed onto the coated membrane. The structure is then heat treated.

[0041] Returning to describing the printing technique, a printable composition suitable for use in the present invention is prepared by thoroughly mixing the catalyst particles with one or more binders in an aqueous or organic vehicle (e.g., in a water-miscible alcohol) or a mixture thereof. As used herein, the term "printable composition" refers to a mixture that exhibits the necessary physical properties, such as flowability and thixotropy, for use in printing techniques such as screen printing, stencil printing, inkjet printing, and roller-coating.

[0042] The concentration of catalyst in the printable composition of the present invention is preferably not less than 1%, for example 5% to 80% (w / w). Catalysts operable in the process of the present invention include (but are not limited to) silver particles, such as silver powder associated with zirconium oxide as disclosed in US 8,142,938. The characteristics of this particular type of silver particles are as follows: average primary particle size of 40 to 60 nm; average agglomerate size of 1 to 25 μm; average agglomerate porosity of about 38 to 45%, zirconium oxide content of 0.2 to 4% (w / w) and specific surface area of ​​4 to 10 m 2 / g. The particles are of high purity, that is, the content of silver and ZrO2 is not less than 99.9%.

[0043] Other suitable catalysts for promoting oxygen reduction include platinum, tungsten carbide, cobalt, manganese dioxide, spinel compounds, perovskite compounds (i.e., mixed metal oxides having the molecular formula ABO3, wherein A and B are cations of two different metals, and wherein the A cations are coordinated to twelve oxygen atoms, and the B cations occupy octahedral sites and are coordinated to six oxygen atoms), carbon-based particles (such as carbon black in combination with platinum, palladium and silver). Mixtures of the various catalysts set forth above may also be used.

[0044] The concentration of the binder in the printable composition of the present invention is preferably not less than 1%, for example 1% to 30% (w / w). The binder combined with the catalyst particles to form the printable composition can be hydrophobic and can be used for several useful purposes. The binder is capable of forming a uniform composition with a paste-like consistency. The binder can be hydrophobic so that it helps to attach the PTFE sheet layer that forms a part of the electrode assembly of the present invention. The binder can also contribute to the hydrophobic properties of the electrochemical reaction zone, which is composed of a solid catalyst (e.g., silver particles), an alkaline electrolyte, and air. Suitable binders include fluorinated polymers and copolymers, such as fluorinated ethylene propylene copolymers (abbreviated herein as "FEP"), which are copolymers of hexafluoropropylene and tetrafluoroethylene, and are therefore compatible with the applied PTFE separator. Other suitable binders include PVDF (polyvinylidene fluoride), PFA (perfluoroalkoxy), THV (copolymer of tetrafluoroethylene, hexafluoropropylene, and vinylidene fluoride), polyethylene (such as coathylene or chlorotrifluoroethylene).

[0045] The printable composition also comprises a liquid carrier, which is preferably composed of an aqueous alcohol, such as a mixture of water and ethanol or water and isopropanol. Preferably, water and alcohol are used in approximately equal volumes.

[0046] The printable composition is prepared by combining a catalyst, a binder and a liquid carrier. To this end, the binder is conveniently applied in the form of an aqueous dispersion, the binder being first mixed with the catalyst, then water and alcohol are added and the resulting composition is vigorously stirred until a paste is formed. The mixing may be interrupted intermittently, allowing the composition to stand for no more than 60 minutes after each interruption.

[0047] It should be noted that one or more additional ingredients may be present in the printable composition, such as conductive powders, for example carbon, graphite, nickel, nickel-coated carbon, tungsten carbide or titanium oxides or nitrides. Generally, the weight concentration of the additive(s) in the printable composition is 0% to 80%.

[0048] The amount of printable composition per unit area of ​​the current collector is preferably 10 mg / cm 2 Up to 150mg / cm 2 .

[0049] Back to Figure 4, a tray (25) in the form of a relatively thick hydrophobic support sheet (e.g., polypropylene, polyethylene, silicon or thicker PTFE sheet), a current collector (23) and a template with a thickness of about 50 microns to 1mm are stacked on each other on the working surface of the printer. The printable composition is then applied to the surface of the stainless steel template, the template is then removed, and a suitable covering is placed above the current collector. The compaction of the catalyst is then completed in a press. For this reason, the structure consisting of a mechanical tray, a current collector loaded with electrode particles and a cover is transferred to a press, wherein a pressure of 0.5-35 tons is applied to convert the electrode particles into a compacted material (mass) embedded in the central region of the current collector. The cover is then peeled off from the current collector of the loaded catalyst, and the current collector is then separated from the mechanical tray (e.g., with a polypropylene sheet). The resulting element is composed of a current collector having catalyst particles fixed in its central region.

[0050] It should be noted that the stages described above include several steps (e.g., assembling a mechanical tray and a current collector, then printing a catalyst formulation), and the order of these steps can be reversed. For example, the catalyst composition (26) is printed directly on the surface of the mechanical tray (e.g., on a polypropylene sheet (25)). The current collector (23) is then placed on the printed area so that the side of the conductive metal frame (22) is aligned with the side of the printed area. The current collector is then pressed on the area where the catalyst is printed, whereby the catalyst penetrates into the holes of the current collector. The temporary polyethylene sheet tray is then disassembled from the electrode, and excess electrolyte is removed.

[0051] An important feature of the invention is that the printable composition is not applied over the entire central area of ​​the current collector. During the printing stage, a narrow gap of about 1-7 mm is left between the periphery of the current collector and the border of the area filled with active material using appropriate masking.

[0052] The operation described above, i.e. the introduction and compaction of the catalyst and the coupling of the hydrophobic membrane can also be carried out substantially simultaneously, so that there is no need to use a temporary removable tray. In this modification of the present invention, the hydrophobic PTFE membrane is supported on a suitable substrate, for example, a substrate of silicon-coated PTFE membrane weakly attached thereto. The printable composition is applied to the upper surface of the PTFE membrane. Then the current collector is placed on the PTFE membrane (it should be noted that the application of the printable composition and the placement of the current collector can be implemented in the opposite order), and the cathode of the single grid obtained is pressed under the conditions described above.

[0053] After compaction in the press, the electrode assembly is baked and sintered at the highest allowable temperature for a period of about 5 to 30 minutes, which temperature is about 230°C-360°C, preferably 230°C-300°C, and more preferably about 250°C-280°C. It should be noted that the hydrophobic PTFE membrane does not easily withstand the conditions encountered during the sintering stage and tends to detach from the current collector. The attachment of the PTFE membrane to the surface of the current collector can be promoted in the following ways: mechanically, such as using a releasable fixing member, such as a simple clip that holds the PTFE membrane around the electrode assembly; or chemically, by increasing the amount of binder present in the printable composition used to form the electrode. In particular, the use of FEP as a binder in the printable composition allows a relatively low operable sintering temperature.

[0054] According to the above-described variant of the invention, a commercially available hydrophobic membrane is attached to an electrode to form an electrode assembly. However, in some cases, such as when it is found that a commercially available membrane exhibits a high shrinkage rate or when it is necessary to improve the contact between the catalyst layer and the hydrophobic layer, it may be advantageous to form a hydrophobic coating in situ on the electrode instead of using a membrane. Related technology is described in WO 2014 / 057483.

[0055] The electrode comprises: a catalyst for promoting oxygen reduction, the catalyst preferably consisting of silver associated with zirconium oxide as described above; and a binder, the binder preferably being FEP, wherein the weight ratio between the catalyst and the binder is preferably not less than 6: 1. For example, the catalytically active composition contains the binder in an amount of 4 to 15%, more preferably 5 to 14%, even more preferably 5 to 13% (w / w).

[0056] Now go to Figure 5 , which provides a schematic isomorphic view of the key elements involved in the final step of the process, namely, the step of bonding the air cathode (20) to the cell frame (100) by incorporating molten thermoplastic into the pores in the catalyst-free areas of the air cathode with the aid of a press (40) and a hot shoe (50).

[0057] exist Figure 5 In the particular embodiment shown, the geometry of the air cathode is similar to that previously described in Figure 4 The shape of the collection of rectangles shown in FIG. 2 is slightly different. The opposite parallel sides are not equal (to each other); thus, the shape of the air cathode is a pentagon (although not equilateral). Another difference is that the entire current collector frame 22 surrounds the air cathode. Note that Figure 5 The catalytically active surface of the air cathode (20) is not shown in the figure because it faces the cell frame (100) which is placed below the air cathode from the position of the press (40).

[0058] The battery frame (100) is made of a thermoplastic such as polypropylene, including grades reinforced with carbon or glass fibers. Other suitable thermoplastics that can withstand the hot alkaline electrolyte and elevated operating temperatures during operation of the metal-air battery include polyethylene, FEP, FPA, blends of polyphenylene ether resin and polystyrene (Noryl™ available from Sabic), and polyvinyl chloride (PVC).

[0059] The design of the cell frame (100) is fairly conventional except that it features the presence of a raised area (101) which is geometrically identical to the catalyst-free margin area of ​​the PTFE membrane.As mentioned above, the frame (100) is typically molded in one piece, such as by injection molding. Figure 5 The main conventional components shown in FIG. 1 include: an electrolyte inlet (102) to supply electrolyte into the cell cavity; a cylindrical channel (102) having a diameter of ∼30–40 mm; a connector (103) located at one corner of the cell frame; and an anode inlet (104) for introducing a consumable aluminum anode into the middle of the cavity defined by the cell frame (100). It should be noted that an array consisting of a pair of cathode assemblies (20) is typically used, one cathode assembly such as Figure 5 As shown, it is positioned on the upper face of the battery frame (100), and another cathode assembly covers the bottom of the battery frame (not shown), wherein an aluminum anode is inserted in the space between a pair of cathodes; in this case, each opposite side of the battery frame (100) includes a raised portion (101) to enable welding of the cathode (20) on each side. As mentioned above, the frame (100) is usually made in one piece, such as by injection molding, but the frame (100) and the raised portion (101) can exhibit different melt flow properties; that is, the melt flow index (MFI) of the polypropylene grade from which the main body of the frame (100) is made is 10 to 20 g / 10min (ASTM D1238, at 230°C / 2.16kg), while the MFI of the polypropylene (101) forced to penetrate into the pores of PTFE can be greater, such as greater than 30 g / 10min, or greater than 40 g / 10min, or greater than 50 g / 10min.

[0060] The cathode assembly (20) is placed on the plastic frame (100) so that the catalyst-free area (27) on the PTFE coincides in position with the protruding rim of the thermoplastic defining the raised area (101). The width of the plastic rim (101) is 3-5 mm, while the surface of the exposed PTFE, i.e. the surface of the catalyst-free area (27), is slightly larger, preferably 4-8 mm in width. The height of the rim is 1-3 mm.

[0061] The cathode is placed in a hot press having a mold (50) (a hot shoe made of aluminum) which corresponds in geometry and size to the raised portion (101). Therefore, the width of each side of the mold (50) is equal to or slightly less than the width of the exposed catalyst-free area. The shoe mold (50) is preferably made of aluminum. The temperature of the hot shoe is higher than the melting temperature of the plastic frame (for example, in the case of PP, the preferred temperature range of the hot shoe can be 140°C-280°C). As mentioned above, the catalyst side of the electrode faces the frame, while the PTFE side is exposed toward the press. A heat release pad can be used to prevent the hot shoe from sticking to the PTFE membrane. A preferred choice is 0.15 mm impregnated glass cloth of PTFE.

[0062] The press (40) is activated and presses the heated mold (50) onto the electrode. The pressing pressure and the compaction distance can be controlled to establish the welding head pressure while allowing the pressing head to extend as the plastic rim thermoplastic melts. The preferred pressure is generally 1 to 100 kg / cm 2 The flow of the thermoplastic is directly related to the type of thermoplastic used, the weld tip temperature and the pressure applied. By building up the pressure correctly, the flow of the thermoplastic is in the direction of the PTFE membrane. It is best to place a stopper within the weld area to eliminate extension of the weld tip beyond a certain distance. Welding times are typically between a few seconds and a minute or two.

[0063] Thermal welding systems used instead of direct thermal welding include ultrasonic welding, radio wave welding, pulse welding, induction welding, solvent welding or laser welding.

[0064] During the welding process, the thermoplastic melts and flows through the mesh or expanded metal (i.e. Figure 4 The current collector 23; Figure 5 The PTFE film is formed by a molten thermoplastic (not shown in Figure 100 because it faces the frame 100) and fills the PTFE pores to some extent in the catalyst-free area 27. The molten thermoplastic flows into the PTFE pores and its solidification combines the PTFE film and the thermoplastic. It can be seen that when the PTFE film is torn off the thermoplastic rim, a residue of PTFE remains on the rim, indicating good adhesion of the PTFE to the thermoplastic rim. The thermoplastic may contain conventional additives, such as mechanical property modifiers, processing modifiers, etc.

[0065] During the welding process, the footprint of the welding shoe is very thin (typically a few millimeters). It is generally recommended to eliminate heat flow to the active electrode area. Heat flowing into the active area of ​​the electrode may damage the catalyst and cause oxidation of the catalyst or delamination of the PTFE film from the active electrode. We have found it to be advantageous to place a heat sink over the active area of ​​the electrode to absorb excess heat flowing from the hot shoe through the catalyst. The simplest method may be a pad soaked in water; however the preferred method is a metal heat sink with a cooling cryogenic liquid flowing through the metal to ensure low temperatures and efficient heat absorption rates.

[0066] As Figure 5 As an alternative to the method shown in (based on a raised thermoplastic portion (rim 101) forming an integral part of a molded plastic cell frame (100), one could consider a pre-cut piece of polypropylene corresponding in shape and size to the rim (101). This piece could be placed between a conventional cell frame (100) and a cathode assembly (20); with the application of heat and pressure as described above, the same effect of flow and penetration of molten polypropylene into the pores of the PTFE membrane would be achieved.

[0067] Electrodes produced in this way have been exposed to 30% potassium hydroxide solution at 80°C in a closed circuit. The pressure of the system was varied arbitrarily between 50 mbar and 300 mbar. The appearance of electrolyte flow from the cell tracked the leakage of the welding line. These electrodes have achieved more than 300 operating hours without any signs of leakage.

[0068] Figure 6 The diagram shows a primary thermoplastic (i.e., a raised polypropylene region; Figure 6 A combination of an air cathode (indicated as PP ribs in the figure) and a hot melt polyolefin (preferably in the form of beads; indicated as polyolefin beads) is used for welding the air cathode to the cell frame. Figure 6 A cross section of a cell frame is shown; it can be seen that each of the opposing sides of the cell frame includes a combination of raised polypropylene portions and hot melt polyolefin to enable welding of the cathode on each side, as explained above. The hot melt polyolefin is applied so that it surrounds the raised polypropylene portions, for example, creating a surrounding raised polypropylene portion. The polyolefin selected is a polyolefin bonding adhesive that can bond well to polypropylene. It should not liquefy at the highest operating temperature of the battery (e.g., up to 80°C). The polyolefin beads are injectable at temperatures above 160°C, such as above 180°C. Suitable hot melt polyolefins in bead form are commercially available, for example from 3M TM Polyolefin bonding adhesive 3731.

[0069] Example

[0070] Preparation 1

[0071] Printable catalyst formulations

[0072] Silver catalyst (70 grams; prepared as described in US 8,142,938) was mixed with 10 grams of FEP (available from Dupont as an aqueous dispersion, TE-9568). The mixture was placed in a rotary shaker for 1 hour. Water (20 grams) and isopropyl alcohol (20 grams) were then added to the mixture and the shaker was allowed to rotate for an additional period of 25 minutes. The resulting composition was allowed to stand for 1 hour and then mixed for an additional 25 minutes. The resulting composition exhibited good fluidity and thixotropy and was suitable for use as a printable material.

[0073] Preparation 2

[0074] Printable catalyst formulations

[0075] A silver catalyst (70 grams; prepared as described in US 8,142,938) and 70 grams of nickel-plated carbon particles (60% w / w, such as E-2701 or E-2702 commercially available from Sulzer) were mixed with 14 grams of FEP (available from DuPont as an aqueous dispersion, TE-9568). The mixture was placed in a rotary shaker for 1 hour. Water (40 grams) and ethanol (40 grams) were then added to the mixture, and the shaker was allowed to rotate for an additional 25 minutes. The resulting composition was allowed to stand for 1 hour and then mixed for an additional 25 minutes. The composition so formed exhibited good flow and thixotropy and was suitable for use as a printable material.

[0076] Example 1

[0077] Air electrode assembly having thermoplastic applied to a delimited area of ​​a PTFE membrane

[0078] Preparation of current collector : Nickel mesh (commercially available from Haver & Bocker (nickel 99.2 nickel lead, 34 mesh, lead thickness 250 μM, rolled to 0.23 mm thick) was cut into pentagonal meshes (shaped like Figure 5 a = 22.5 cm, b = 18.5 cm, c = 13.5 cm, d = 10.0 cm and e = 5.0 cm). The resulting mesh was thoroughly cleaned with ethanol and the metal particles were blown away from the mesh using air pressure.

[0079] The 500 μm thick copper sheet was cut into pentagonal frames ( Figure 5 22 in the copper piece). A conductive sheet 24 (2.5 cm x 3 cm) is attached to one side of the copper piece. The copper sheet is then plated with nickel by electroless nickel plating, forming a nickel coating of about 20 microns thick.

[0080] Then, a nickel-plated pentagonal copper frame 22 is welded to the edge of the nickel mesh by spot welding (resistance welding).

[0081] Preparation of electrodes: The catalyst preparation (see Preparation) was applied to the current collector as follows. A 200-300 μm thick polypropylene sheet, current collector and a 200-300 μm thick polypropylene sheet with a cavity of appropriate size was applied to the current collector. A 500 μm stainless steel template (to be able to form a catalyst-free margin area) is placed on a printer (Ami Presco MSP-9155 model) so that the polypropylene sheet and the stainless steel template constitute the bottom and top layers, respectively. The catalyst preparation is then applied using a blade or scraper, which passes over the template so that the silver catalyst preparation penetrates through the template into the holes of the current collector mesh. The stainless steel template is then removed, and 10 standard A4 papers are placed over the current collector and the stack is transferred to a press, where a pressure of 10 tons is applied. The paper is carefully peeled off from the electrode, and then the electrode is detached from the polypropylene sheet.

[0082] Electrode assembly :The electrodes are combined with the hydrophobic membrane as follows. The outer periphery of the Haber & Bocker mesh is coated with an aqueous form of FEP (such as TE9568 or FEPD121 produced by DuPont) via a thin paint brush, and the emulsion is allowed to dry for 10 minutes. A porous hydrophobic PTFE membrane (made by Saint Gobain or Gore) slightly larger than the electrode is placed over the electrode, and a pressure of 10 tons is applied using a press. The electrode assembly is then baked and sintered at about 280°C for a period of about 20 minutes. In order to prevent the diaphragm from shrinking or detaching from the mesh, a heavy external metal frame that coincides with the outer area of ​​the current collector is placed on the mesh and diaphragm, thereby reducing the detachment of the diaphragm during the sintering process at 280°C.

[0083] The electrodes were allowed to cool to room temperature before being welded to the battery frame.

[0084] Welding the air cathode to the battery frame

[0085] Set as Figure 5 The electrode assembly (20) with the exposed area of ​​PTFE is placed on a thermoplastic frame (100) of polypropylene. The side of the electrode assembly with the catalyst layer applied thereon faces the thermoplastic frame, so that Figure 5 Towards the outside is a PTFE membrane. The frame can be filled with plastic or metal inserts so that the plastic does not bend when exposed to high pressure and temperature.

[0086] A polytetrafluoroethylene (Teflon) based sheet [available from The hot press (40) with the hot shoe (50) was heated to 260°C and heated at 10-15 kg / cm 2 The pressure of 1000 g was applied to the hot shoe. The pressure was maintained for 30 seconds. The heating head was raised and a brass plate of 4 mm thickness and exactly the electrode size was placed on the electrode for a period of 1-3 minutes until the electrode temperature reached below 80°C.

[0087] Example 2

[0088] Air Electrode Assembly Having Thermoplastic Applied to Delimited Areas of PTFE Membrane The steps of Example 1 were repeated, except that the final step was performed as described below.

[0089] Welding the air cathode to the battery frame

[0090] Set as Figure 5 The electrode assembly (20) with the exposed area of ​​PTFE is placed on a thermoplastic frame (100) of polypropylene. The side of the electrode assembly with the catalyst layer applied thereon faces the thermoplastic frame, so that Figure 5 Towards the outside is a PTFE membrane. The frame can be filled with plastic or metal inserts so that the plastic does not bend when exposed to high pressure and temperature.

[0091] like Figure 6 As shown, a polyolefin hot melt bead is applied to the periphery of the frame, with the polypropylene raised area (101) inwardly and more of a hot melt circle outwardly, (the ribs indicate the polypropylene wall protruding from the surface of the frame). This structure provides a stronger mechanical weld combined with an additional leak barrier.

[0092] A polytetrafluoroethylene (Teflon) based sheet [available from The hot press (40) with the hot shoe (50) was heated to 260°C and heated at 10-15 kg / cm 2 The pressure of 1000 g was applied to the hot shoe. The pressure was maintained for 30 seconds. The heating head was raised and a brass plate of 4 mm thickness and exactly the electrode size was placed on the electrode for a period of 1-3 minutes until the electrode temperature reached below 80°C.

Claims

1. A method for assembling a metal / air battery, comprising the following steps: (i) providing an air cathode assembly, comprising a hydrophobic porous membrane having a first surface and a second surface, wherein a current collector and an active layer containing a catalyst are provided on the first surface, wherein the planar dimensions of the active layer containing the catalyst are smaller than the planar dimensions of the membrane and the current collector, so that the active layer containing the catalyst does not reach the edges of the membrane and the current collector, thereby creating a catalyst-free margin around the active layer containing the catalyst on the membrane and the current collector; (ii) placing the cathode assembly on top of a cell frame defining an electrolyte cavity, wherein a thermoplastic body is positioned between the cell frame and the cathode assembly, the thermoplastic body being capable of softening to a movable, flowable state when heated to an elevated temperature, wherein the thermoplastic body coincides in geometry and position with the catalyst-free margin area and also substantially coincides in width with the catalyst-free margin; (iii) applying heat and pressure to soften the thermoplastic body and force the thermoplastic melt to flow in the catalyst-free confinement of the hydrophobic porous membrane in the direction of the pores, thereby welding the air cathode assembly to the frame of the cell when the melt solidifies, Wherein, the thermoplastic body includes a raised portion of the battery frame protruding from a surface of the frame, the raised portion forming an integral part of the frame.

2. The method according to claim 1, comprising the steps of: A hot melt polyolefin is applied to the surface of the battery frame adjacent to and in a direction outward from the raised portion of the battery frame.

3. The method according to any one of claims 1 to 2, wherein: The thermoplastic body is a polypropylene body.

4. The method according to any one of claims 1 to 3, wherein: The thermoplastic body softens at a temperature ranging from 120°C to 280°C.

5. The method according to any one of claims 1 to 4, wherein: The air cathode is welded to the frame of the cell by coating the current collector with molten thermoplastic and / or by allowing the molten thermoplastic to penetrate into the pores of the hydrophobic membrane in the catalyst-free margin.

6. The method according to any one of claims 1 to 5, wherein: The hydrophobic membrane is a PTFE membrane.

Citation Information

Patent Citations

  • Electrochemical device utilizing an electrode comprising a continuous PTFE film which is gas permeable and free from liquid electrolyte seepage

    US3553024A

  • Primary aluminum-air battery

    US4925744A

  • Porous clusters of silver powder promoted by zirconium oxide for use as a catalyst in gas diffusion electrodes, and method for the production thereof

    US8142938B2

  • Electrode assembly and method for its preparation

    WO2014057483A1

  • Cathode structre of lithium-air battery and method for manufacturing cathode of lithium-air battery

    CN104241731A